Influence of local postbuckling behaviour on bending of thin-walled beams - Manevich, Arkady; Kolakowski, Zbigniew (Thin-walled structures, 1996)
The influence of the local postbuckling behaviour on the bending of thinwalled beams is studied. The analysis of the postbuckling behaviour of a prismatic column-beam subject to compression and bending is employed in order to determine the overall flexural stiffness of a beam after local buckling. The asymptotic Koiter method is used in the second order approximation. The determination of post-buckling coefficients enables one to find the beam's flexural stiffness without the necessity of using hypotheses on effective widths of eccentrically compressed plates. It is shown that the post-buckling equilibrium branch in a bending moment-global curvature coordinate system for a perfectly elastic thin-walled beam is rectilinear (in the second order approximation of' the asymptotic method). Simple analytical relations are presented between the slope of the post-buckling equilibrium branch of global bending and post-buckling coefficients for local buckling mode. The results obtained are compared with data reported by other authors.